THE EFFECT OF CAPITAL STRUCTURE, TATO, RESEARCH AND DEVELOPMENT,: INFLATION DAN INTEREST RATE AGAINST FINANCIAL DISTRESS - Marchelina, Eva; Hutapea, Ganda T.; Anggraini, Nenny (Universitas Kristen Indonesia, 2017)
The purpose of this study is to determine the effect of capital structure, TATO, research and development, inflation, and interest rate against financial distress. Interest Coverage Ratio is used to determine beginning signs of financial distress in GB company. Researchers used statistic descriptive and binary logistic regression method, the data is sampled using purposive sample judgment method. This study used data of 10 GB companies which has been listed on the Indonesia Stock Exchange (BEI) on period of 2013 – 2015 and totally this study used 30 samples of 10 GB companies on period of 2013 – 2015. The results of this study found that capital structure, research and development, inflation, and interest rate effect uninfluence on financial distress. Then TATO influence the level of financial distress.Keywords: Financial Distress, Macro Economics, Research and Development, Total Asset Turnover (TATO), Capital Structure, Interest Covarage Ratio (ICR).